Etiological Profile of Hyperbilirubinemia in Full Term Neonates Requiring Exchange Transfusion - Khan, Muhammad Faizullah; Nawaz, Asif; Khan, Wajid; Abbasi, Vildan Zaheer; Amin, Sadiq; Khan, Farhan Zeb (Biological and Clinical Sciences Research Journal, 2025)
Neonatal hyperbilirubinemia, characterized by elevated serum bilirubin, is common in full-term neonates, with severe cases requiring exchange transfusion to prevent complications like kernicterus. This study explores the etiological factors necessitating this intervention at Ayub Teaching Hospital, Abbottabad. Objective: To identify and analyze etiological factors of hyperbilirubinemia requiring exchange transfusion in full-term neonates. Methods: A descriptive cross-sectional study was conducted at Neonatology Unit, Ayub Teaching Hospital, Abbottabad, from 2 December 06 May 2025, enrolling 385 full-term neonates (gestational age 37–42 weeks) with serum bilirubin >19.5 mg/dL. Data on demographics, clinical profiles, and etiologies were collected and analyzed using SPSS version 22. Results: ABO incompatibility (36.1%) was the leading cause, followed by Rh incompatibility (24.2%), G6PD deficiency (11.7%), sepsis (10.6%), and intracranial bleeding (3.4%). Unidentified causes accounted for 14.0%. Most neonates (93.8%) were discharged stable post-transfusion. Conclusion: ABO and Rh incompatibilities predominate, highlighting the need for enhanced antenatal screening and early neonatal surveillance to reduce exchange transfusion necessity.